3+3s-(4s+1)-(2s+6)=

Simple and best practice solution for 3+3s-(4s+1)-(2s+6)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3+3s-(4s+1)-(2s+6)= equation:


Simplifying
3 + 3s + -1(4s + 1) + -1(2s + 6) = 0

Reorder the terms:
3 + 3s + -1(1 + 4s) + -1(2s + 6) = 0
3 + 3s + (1 * -1 + 4s * -1) + -1(2s + 6) = 0
3 + 3s + (-1 + -4s) + -1(2s + 6) = 0

Reorder the terms:
3 + 3s + -1 + -4s + -1(6 + 2s) = 0
3 + 3s + -1 + -4s + (6 * -1 + 2s * -1) = 0
3 + 3s + -1 + -4s + (-6 + -2s) = 0

Reorder the terms:
3 + -1 + -6 + 3s + -4s + -2s = 0

Combine like terms: 3 + -1 = 2
2 + -6 + 3s + -4s + -2s = 0

Combine like terms: 2 + -6 = -4
-4 + 3s + -4s + -2s = 0

Combine like terms: 3s + -4s = -1s
-4 + -1s + -2s = 0

Combine like terms: -1s + -2s = -3s
-4 + -3s = 0

Solving
-4 + -3s = 0

Solving for variable 's'.

Move all terms containing s to the left, all other terms to the right.

Add '4' to each side of the equation.
-4 + 4 + -3s = 0 + 4

Combine like terms: -4 + 4 = 0
0 + -3s = 0 + 4
-3s = 0 + 4

Combine like terms: 0 + 4 = 4
-3s = 4

Divide each side by '-3'.
s = -1.333333333

Simplifying
s = -1.333333333

See similar equations:

| -8y-1=-7y-6 | | 6x-12=16x-8 | | 2/3k=28.4/9 | | 2r-3s=-8 | | 2c+4=20 | | -35x^2+2x-1=0 | | (-3a-7)-(-a+9)= | | 7x-2yforx-5andy=3 | | (8y^5)1/3 | | 8-5=4p-1 | | 3(y-5)=2y+2 | | 3x-y=22x-y=3byelimination | | cos(3x)+cos(5x)=0 | | 60x^2y-70x^4zw= | | 34-79=x | | 343-79=x | | 4k+3k+90+174=360 | | 28=.5x^2 | | Y=-6.75+8.54 | | 8(4q-5)-7q=2q-10 | | 13y+15=11x-25 | | x-79=2 | | 4k+3k=96 | | (3n+8)+n=54 | | 6(2+-1)+5=12-t | | (3/5x)^-1 | | 6(x*3)=21 | | 4p=160 | | 9r+6r+3=6r+3-r | | 2n+3(15)= | | 9x^2+24x+0=0 | | 2(8s+9)-4s=3(4s+5)-20 |

Equations solver categories